2016
DOI: 10.3892/ol.2016.4187
|View full text |Cite
|
Sign up to set email alerts
|

Elevated matrix metalloproteinase-9 expression may contribute to the pathogenesis of bladder cancer

Abstract: Abstract. The present study investigated the potential association between matrix metalloproteinase-9 (MMP-9) expression and the pathogenesis of bladder cancer. The present study reviewed previous studies published in Chinese and English using predefined selection criteria, which identified high-quality studies concerning MMP-9 and bladder cancer. Statistical analyses of the data were conducted using Comprehensive Meta-Analysis software version 2.0. In total, 23 case-control studies were selected, which consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Our results showed that the upregulation of MMP9 and S100A8 gene and protein levels correspond to the OPN overexpression and downregulation of these genes/proteins with knockdown of OPN. Matrix metalloproteinase, (MMP) family is an important ECM-degrading proteinase 7 , 46 , 47 and one of metalloproteinase activities is to facilitate cell migration 48 . ECM, however, consists a barrier that prevents migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the upregulation of MMP9 and S100A8 gene and protein levels correspond to the OPN overexpression and downregulation of these genes/proteins with knockdown of OPN. Matrix metalloproteinase, (MMP) family is an important ECM-degrading proteinase 7 , 46 , 47 and one of metalloproteinase activities is to facilitate cell migration 48 . ECM, however, consists a barrier that prevents migration.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 has been reported to be involved in the pathogenesis of bladder cancer and other cancers when it is upregulated 47 , 52 . Both pro-MMP9 and its active form have a PEX-domain that either docks or/and form heterodimeratization with the surface receptor, CD44 in the OPN molecule of T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is a potent proteolytic enzyme and plays a key role in degradation of basal membranes and the extracellular matrix, through cleaving type IV collagen and gelatin, which are the main structural components of the basal membrane. The proteolytic activity of MMP9 is not only to induce invasion and metastasis, but also to generate matrix-bound growth factors and other signaling molecules responsible for growth signaling, angiogenesis and an inflammatory response [40][41][42]. Again, ELISA results showed that serum concentration of MMP-9 is associated with malignant grade of bladder cancer (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…These significant findings implied the predictive role of MMPs in poor outcome of bladder carcinomas [ 33 35 ]. The majority of current investigations have provided strong evidence for the oncogenic role of MMPs in human bladder cancer.…”
Section: Discussionmentioning
confidence: 99%